2010
DOI: 10.1007/s10856-010-4089-2
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic investigation into the setting and mechanical properties of titanium containing glass polyalkenoate cements

Abstract: Titanium (Ti) implants are extensively used in a number of biomedical and dental applications.This work introduces Ti into the glass phase of a zinc based Glass Polyalkenoate Cement (GPC) and investigates changes in handling and mechanical properties considering two molecular weight polyacrylic acids (PAA), E9 and E11. Considering the handling properties, the working time (T w ) increased from 50s E9 , 32s E11 (BT 101, Ti-free) to 169s E9 , 74s E11 with TW-Z (highest Ti content) respectively. The setting ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Figure 5 shows the SA of the cements over 1 & 30 days. these materials found that the Ti cements are more structurally stable when set than the Ti free cement, BT 101, which is the likely reason for the reduced loss in SA as compared to BT 101 [31] .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Figure 5 shows the SA of the cements over 1 & 30 days. these materials found that the Ti cements are more structurally stable when set than the Ti free cement, BT 101, which is the likely reason for the reduced loss in SA as compared to BT 101 [31] .…”
Section: Resultsmentioning
confidence: 93%
“…The bioactive response of a series of Ti substituted GPCs was evaluated to expand previous work which described the glass phase characterization [32] , mechanical properties and setting of these cements [31] . Initial testing was performed on the glass both before and after γ-sterilization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work by the authors has seen the development of a SiO 2 -CaO-SrO-ZnO based GPC series for orthopaedics, in particular for stabilization of osteoporotic vertebral augmentation such as Vertebroplasty and Kyphoplasty [29][30][31][32]. Some properties of these materials, including mechanical and rheological properties and bioactivity were further improved by subsequently substituting titanium (Ti) for the silica content within the glass phase [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…28 Until recently, the development of aluminum-free GICs that provide clinically useful handling (5-10 min of injectability) and strength (>30 MPa in compression) for VP and KP has proven challenging. [29][30][31][32][33][34][35] In 2013, Dickey et al was the first group to publish germanium-inclusive zinc-based GICs with a range of properties that encompasses those required for these applications, marking a major advancement in the aluminum-free GIC literature, and the first set of clinically viable GICs for use in this regard. 27 In keeping with the emerging philosophy that injectable bone cements used in the management of cancerrelated VCFs must address both the fracture and the underlying pathology, this study seeks to expand the therapeutic benefits of aluminum-free GICs through investigating their drug delivery potential.…”
Section: Introductionmentioning
confidence: 99%